An indication of salt caprock failed integrity in inclusion records: Dongpu depression, bohai bay basin, China. (February 2023) - Liu, Xiuyan; Chen, Honghan; Huang, Yahao; Safaei-Farouji, Majid; Ostadhassan, Mehdi
Abstract: Salt rocks are widely distributed in the Paleogene strata of the Dongpu Depression, China, as major caprocks of the Shahejie Formation. Previous studies have suggested that the decline of formation pressure during the Dongying movement is accompanied by petroleum leakage, but they lack any direct evidence of failed integrity of the salt caprocks. Therefore, fluid inclusion analysis under both incident ultraviolet (UV) and transmitted light (TR) modes on halite samples were conducted in this study, supported by basin and fluid inclusion PVTX modeling to prove lack of integrity in the caprock, periodically. Our observation showed that various types of hydrocarbon inclusions exist in halite crystals, revealing multi-stage fracturing and healing processes inside the salt caprocks. Coupling the PVTX and basin modeling results, revealed that oil inclusions were trapped at around 6.6 Ma during the secondary hydrocarbon generation of the source rocks. Moreover, salt caprocks failed due to the overpressure that was formed during hydrocarbon generation. This was exacerbated by the following uplifting which ultimately led to the present-day normal reservoir pressure in the sampled depth. In addition, the fluorescence of oil inclusions in the same fracture gradually changed from orange to blue. This proved that analyzing the thermal maturity of trapped hydrocarbons within the inclusions, solely based on the fluorescence color, could be misleading and other submicron scale analytical methods should be employed to examine the inclusions. Overall, this study enabled us to investigate the caprock integrity via optical methods, which can eventually help us to avoid regions where hydrocarbon is lost vs. prolific areas in the formation understudy. Highlights: FIA under incident UV and TL on halite proved lack of integrity in the caprock, periodically. Various hydrocarbon inclusions revealed a moderate overpressure succeeding pressure release during the following Uplift. Changing oil fluorescence color proves analysis of maturity is misleading solely based on this criteria.